Ações e fundos de investimentos em ações: fatores de riscos comuns ? - Rocha, José Alan Teixeira da (2008)
In this article, was analyzed the capacity of valuation and forecast on the main stock investment funds in the Brazilian market, using the Capital Asset Pricing Model (CAPM), the Fama e French (1993) factor model and the Carhart (1997) four-factor model. According to the results, we have a better performance of the CAPM vis-à-vis the factor models, even for the investment funds that over perform the market. This result can be seen as an evidence of the necessity to develop a factor model a la Fama and French, but specific for investment funds.